Using Apps to Support Disciplinary Literacy and Science Learning. Issue 7 (27th March 2013) - Castek, Jill; Beach, Richard
Abstract: Apps, specialized programs used on mobile computers, can be used in innovative ways to enhance science and literacy learning. With the skilled guidance of their teachers, students can exploit app affordances for learning and acquire disciplinary literacies unique to science. This article showcases apps that help students to access information, make sense of it, and create their own products that include rich visual representations. We also describe teaching approaches that support the close reading of science texts through the use of note‐taking and annotation apps. Classroom examples that are featured illustrate that these app affordances are not simply in the apps, but rather, fostered by how the teachers exploit these affordances to achieve their own particular learning objectives. As we become more familiar with new apps as educational tools, we need to be mindful about how these tools strategically in ways that best enhance our students' own learning. Abstract : FREE author podcast